The Development of E-Magang System for Independent Learning-Independent Campus Program in Universitas Dharmawangsa - Sabrina Aulia Rahmah; Edy Rahman Syahputra (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2022)
A country's development might be represented by its education system. The Indonesian government, through the Ministry of Education, Culture, Research and Technology make a breakthrough through Regulation of Minister of Education and Culture no. 3 of 2020 on the Independent Learning-Independent Campus (Merdeka Belajar Kampus Merdeka / MBKM) program. This policy provides private and state university students an opportunity to enrich and broaden their knowledge and competence in a real life settings. One of the implementations of this program is the industrial internship. In Dharmawangsa University, MBKM policy has been translated into an industrial internship program through collaboration with several companies and industrial sectors. In order to monitor its students activities during the internship, Undhar assigns a permanent lecturer as a field guide lecturer (Dosen Pembimbing Lapangan/DPL). The monitoring system presented in this paper was developed using Agile Scrum, which began with problem identification stage to system testing stage. This method was selected due to easier adjustability, as it allows further development following the needs. This work produced a web-based system for monitoring and reporting students internship activities, allowing students and DPL to communicate more easily related to the students internship activities.